Effects of transdermal tulobuterol on dyspnea and respiratory function during exercise in patients with chronic obstructive pulmonary disease - Ichikawa, Masako; Kodama, Yuzo; Yoshimi, Kaku; Shiota, Satomi; Kotajima, Masaki; Nakajyo, Mami; Seyama, Kuniaki; Fukuchi, Yoshinosuke; Takahashi, Kazuhisa (Journal of Thoracic Disease, 2015)
Background: Poor exercise tolerability is a major barrier to improving the quality of life of patients with chronic obstructive pulmonary disease (COPD). Although COPD is often treated with long-acting β2 adrenergic agonists, few studies have examined their effects on exercise tolerability. Methods: In this study, Japanese COPD patients were treated with 2 mg transdermal tulobuterol, a long-acting β2 agonist, once daily for 4 weeks. Spirometry and exercise tests were conducted at baseline and at the end of treatment. The patients conducted constant load (30 W for 5 min) and incremental load (starting at 10 W and increasing by 10 W every 1 min for 5 min to a maximum load of 50 W) exercise tests on a cycle ergometer. Results: Thirteen patients with stable COPD participated in this study (mean age ± standard deviation (SD), 69.5±9.7 years; smoking history 55.9±27.8 pack-years). Resting spirometric parameters were unchanged at the end of treatment. The maximum Borg scale for dyspnea and the Borg scale slope (BSS) decreased significantly from baseline to the end of treatment. The threshold load of dyspnea (TLD) increased slightly, although not significantly, in the constant load test but not in the incremental load test. There were no changes in respiratory parameters during exercise after treatment. Conclusions: In conclusion, we found that treatment with transdermal tulobuterol for 4 weeks improved self-assessed dyspnea in Japanese COPD patients during constant and incremental exercise tests. This improvement in dyspnea may encourage patients to perform daily life activities or regular physical activity.